Kualitas Penyajian Bahan Makanan Guna Meningkatkan Kualitas Gizi Anak Binaan di LPKA - Michael Bramulia Tarigan; Ali Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Providing adequate food for detainees, children and detainees in Detention Centers (Rutan), Special Child Development Institutions (LPKA), and Correctional Institutions (Lapas) is a service of the Ministry of Law and Human Rights to guarantee the basic rights of prisoners and children . "This obligation includes not only guaranteeing rights but also ensuring food for all detainees, children and convicts, while currently there are still constraints in the budget which is still insufficient," said Emin Muhaimin. The aim of this research article is to understand, explain and analyze the quality of food presentation in order to improve the nutritional quality of assisted children in LPKA. This article was written using literature study. The data needed was collected through text study, then analyzed using content analysis techniques. Based on literature studies, it shows that quality efforts to serve food ingredients include the process of serving food ingredients, managing nutritional quality, and optimizing the suitability of nutritional standards for assisted children in LPKA. It is necessary to pay attention that budget limitations can affect the quality of food ingredients for assisted children in LPKA.